Principles and practices of method validation - Fajgelj, A. (Aleš); Ambrus, Á. (Árpád) (Special publication (Royal Society of Chemistry (Great Britain)), 2000)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity.